Program to "learn strategically" with university students: Design and experimental validation - Carbonero, Miguel A.; Román, Jose M.; Ferrer, Marisela (Anales de Psicología / Annals of Psychology, 2013)
Teaching cognitive learning strategies to optimize the cognitive processes of students is an important way -simultaneously- optimize the performance of students and improve teaching skills of teachers. Within this framework, we designed and validated an integrated curriculum program, to "learn strategically" used in the organizational, elaboration and expansion strategies. Validation was conducted with 189 university students. 96 in the experimental group and 93 in the control group. We used a quasi-experimental design of two groups with pretest, intervention and posttest. The intervention lasted three months (twelve sessions of two hours); procedure: initial presentation, modeling, guided and independent practice, and feedback. The contents studied were the subject of Developmental Psychology. The program produced significant effects (experimental group- Program "learn strategically" vs. control group-traditional teaching) in elaboration strategies, expansion strategies and specific performance on the issues discussed during the quarter. The validated program, a contribution to the field of instructional psychology, is applicable in higher education classes to help students learn strategies and content simultaneously; and university professors to make educational innovation.